1998
DOI: 10.1016/s0006-3495(98)77558-7
|View full text |Cite
|
Sign up to set email alerts
|

Model for the Light-Harvesting Complex I (B875) of Rhodobacter sphaeroides

Abstract: The light-harvesting complex I (LH-I) of Rhodobacter sphaeroides has been modeled computationally as a hexadecamer of alphabeta-heterodimers, based on a close homology of the heterodimer to that of light-harvesting complex II (LH-II) of Rhodospirillum molischianum. The resulting LH-I structure yields an electron density projection map that is in agreement with an 8.5-A resolution electron microscopic projection map for the highly homologous LH-I of Rs. rubrum. A complex of the modeled LH-I with the photosynthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
137
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 101 publications
(143 citation statements)
references
References 76 publications
6
137
0
Order By: Relevance
“…The F 0 ,F 1 -ATPase is also present, although in a much smaller amount (13). Both LH1 and LH2 tend to form ring structures (14,15). In some bacteria such as Blastochloris viridis and Rhodospirillum rubrum, LH1 forms a closed ring around the RC (16 -18).…”
mentioning
confidence: 99%
“…The F 0 ,F 1 -ATPase is also present, although in a much smaller amount (13). Both LH1 and LH2 tend to form ring structures (14,15). In some bacteria such as Blastochloris viridis and Rhodospirillum rubrum, LH1 forms a closed ring around the RC (16 -18).…”
mentioning
confidence: 99%
“…Although most phototrophic bacteria contain two kinds of light-harvesting complexes, light-harvesting complex 1 (LH1) and light-harvesting complex 2 (LH2), only one of these, LH1, is in intimate contact with the RC. Recent structural studies (6,20,22,25,31,36,37,43,(59)(60)(61) have indicated that the component ␣␤ dimers of LH1, each of which binds two bacteriochlorophyll (BChl) molecules and at least one molecule of carotenoid, form a ring around the RC. For Rhodospirillum rubrum (33,37,59,61) and Blastochloris viridis (previously called Rhodopseudomonas viridis) (60), both of which contain only a single light-harvesting complex, LH1 appears to completely surround the RC.…”
mentioning
confidence: 99%
“…In order to most effectively utilize the sunlight that falls on them, all photosynthetic organisms have a system of antenna complexes surrounding the reaction centers where photosynthesis takes place. The photosystems of purple bacteria, such as Rhodopseudomonas acidophila and Rhodobacter sphaeroides [19], have been most extensively studied [20][21][22] by means of ultrashort pulsed laser spectroscopy [23], X-ray protein crystallography [24], as well as hole-burning and absorption studies [25]. In such systems bacteriochlorophyll is the key light-harvesting pigment.…”
Section: Light-harvesting Complexesmentioning
confidence: 99%